Outsourcing and offshore : an analysis of the academic literature - Oliveira, Mírian (2015)
Outsourcing and offshore are strategies adopted by businesses to manage their Information Systems. There has been an increase in the volume of literature devoted to outsourcing and offshore during the past years. This paper provides a review of articles about outsourcing and offshore published in various journals. This list of journals was obtained by consulting the Journal Citation Report with an impact factor of over 3.0 in the last five years. This research was a survey with data collection from the following journals: Information & Management, Information Systems Journal, Information Systems Research, Journal of Information Technology, Journal of Management Information Systems and MIS Quarterly. The results obtained are: the majority of articles have two or three authors (83,9%); the majority of co-authors work in different universities (73,8%); the majority of the authors are associated with a USA-based university (54,5%). The result of this research assists in the identification of researchers and research gaps in this subject.